Meta-analysis of the New Keynesian Phillips Curve - Katarína Danišková; Jarko Fidrmuc (Institut für Ost- und Südosteuropaforschung (IOS), 2012)
The New Keynesian Phillips Curve has become an inherent part of modern monetary policy models. It is derived from micro-founded models with rational expectations, sticky prices, and forward and backward-looking subjects on the market. Having reviewed about 200 studies, we analyze the weight of the forward-looking behavior in the hybrid New Keynesian Phillips Curve by means of meta regression. We show that selected data and method characteristics have significant impact on reported results. Moreover, we find a significant publication bias including publications in top journals, while we document no bias for the most cited studies and the most cited authors.
urn:nbn:de:101:1-201207106438
Keywords: E31; E52; C32; 330; inflation; New Keynesian Phillips curve; meta-analysis; publication bias; New-Keynesian Phillips Curve; Meta-Analyse